Comparison of ±σ-hole and ±R˙-hole interactions formed by tetrel-containing complexes: a computational study. Issue 7 (19th January 2021) - Ibrahim, Mahmoud A. A.; Telb, Ebtisam M. Z.
Abstract : The characteristics and nature of ± R˙-hole interactions were uncovered for the first time and compared to their ± σ-hole analogs in ˙TF3 ⋯ and W–T–F3 ⋯B/R˙/A complexes. Abstract : For the first time, unconventional ± R˙-hole interactions were unveiled in tetrel-containing complexes. The nature and characteristics of ± R˙-hole interactions were explored relative to their ± σ-hole counterparts for ˙TF3 ⋯ and W–T–F3 ⋯B/R˙/A complexes (where T = C, Si, and Ge, W = H and F, B = Lewis bases, R˙ = free radicals, and A = Lewis acids). In an effort to thoroughly investigate such interactions, a plethora of quantum mechanical calculations, including molecular electrostatic potential (MEP), maximum positive electrostatic potential ( V s, max ), point-of-charge (PoC), interaction energy, symmetry adapted perturbation theory (SAPT), and reduced density gradient–noncovalent interaction (RDG–NCI) calculations, were applied. The most notable findings to emerge from this study are that (i) from the electrostatic perspective, the molecular stabilization energies of ˙TF3 and W–T–F3 monomers became more negative as the Lewis basicity increased, (ii) the most stable complexes were observed for the ones containing Lewis bases, forming − σ-hole and − R˙-hole interactions, and the interaction energies systematically increased in the order H–T–F3 ⋯B < ˙TF3 ⋯B < F–T–F3 ⋯B, (iii) contrariwise, the + σ-hole and + R˙-hole interactions with Lewis acids are more energetically favorable in the order F–T–F3 ⋯A < ˙TF3 ⋯A < H–T–F3 ⋯A, and (iv) generally, the dispersion force plays a key role in stabilizing the tetrel-containing complexes, jointly with the electrostatic and induction forces for the interactions with Lewis bases and acids, respectively. Concretely, the findings presented in this paper add to our understanding of the characteristics and nature of such intriguing interactions.